2021
DOI: 10.3390/metabo11020119
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Reveals Major Differences in the Plasma Metabolome between Colorectal Cancer and Colorectal Adenomas

Abstract: Sporadic colorectal cancer is characterized by a multistep progression from normal epithelium to precancerous low-risk and high-risk adenomas to invasive cancer. Yet, the underlying molecular mechanisms of colorectal carcinogenesis are not completely understood. Within the “Metabolomic profiles throughout the continuum of colorectal cancer” (MetaboCCC) consortium we analyzed data generated by untargeted, mass spectrometry-based metabolomics using plasma from 88 colorectal cancer patients, 200 patients with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 52 publications
3
24
1
Order By: Relevance
“…Twenty-one studies compared CRC directly to healthy control [24][25][26]31,33,36,38,39,[42][43][44][45][46][48][49][50][51][52][53][54]56]. Jing et al and Gao et al, conversely, compared CRC patients to an adenomatous polyp control [32,55] while eleven studies utilized CRC, healthy control, and adenomatous polyp groups [28][29][30]34,35,37,40,41,47,57,58]. Two studies (Geijson et al, Liu et al) did not include a control group [22,23], while Di Giovanni et al compared CRC groups to healthy control in both CRC models as well as CRC remission models, using separate controls but comparing CRC-remission and CRC patients using an Effect Size model [27].…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
“…Twenty-one studies compared CRC directly to healthy control [24][25][26]31,33,36,38,39,[42][43][44][45][46][48][49][50][51][52][53][54]56]. Jing et al and Gao et al, conversely, compared CRC patients to an adenomatous polyp control [32,55] while eleven studies utilized CRC, healthy control, and adenomatous polyp groups [28][29][30]34,35,37,40,41,47,57,58]. Two studies (Geijson et al, Liu et al) did not include a control group [22,23], while Di Giovanni et al compared CRC groups to healthy control in both CRC models as well as CRC remission models, using separate controls but comparing CRC-remission and CRC patients using an Effect Size model [27].…”
Section: Study Design and Population Characteristicsmentioning
confidence: 99%
“…Another study based on stool metabolomics showed that combination of Cer 18:1, Cer 18:2, Cer 20:4, PE 16:0/18:1, SM d18:1/23:0, SM 42:3, and TAG 54:1 could effectively discriminate NR and CRC as the diagnostic biomarker, and its integrated performance was good (AUC = 0.821) (30). In the plasma metabolomics, 48 differential metabolites were uncovered between CA and CRC, mainly including LPCs and PCs, and both of them were down-regulated in CRC (31). In tissue metabolomics, PC 32:1 was suggested as an invaluable biomarker, which could be used for clinical diagnosis for CRC by imaging mass spectrometry (32).…”
Section: Discussionmentioning
confidence: 93%
“…LPEPS oral administration decreased 3-hydroxynonanoyl carnitine in the AOM/DSS-treated mice. A number of studies have shown that carnitine was enriched in colon cancer and type 2 diabetes [ 46 , 55 , 56 , 57 , 58 ], while natural active substance supplementation effectively decreased concentration of carnitine in type 2 diabetes [ 46 , 50 ].…”
Section: Discussionmentioning
confidence: 99%